2022
DOI: 10.3390/ijerph191710799
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Health Behavior Interventions to Prevent and Manage Type 2 Diabetes Mellitus in Asia: A Systematic Review of Randomized Controlled Trials

Abstract: Health behavior interventions implemented in Asian countries often lack economic evaluations that effectively address the problems of type 2 diabetes mellitus. This review systematically assessed the existing literature on economic evaluation of health behavior interventions to prevent and manage type 2 diabetes mellitus for people living in Asian countries. Eligible studies were identified through a search of six bibliographic databases, namely, PubMed, Scopus, Public Health Database by ProQuest, Cumulative I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Cost analyses of diabetes prevention in LMICs have been conducted from various perspectives, based on within-trial or simulation modelling studies [ 58 ], with some of the first analyses coming from the Indian Diabetes Prevention Programme (IDPP) [ 59 ]. In this trial, over the 3 years of the study, the incremental cost-effectiveness ratio (ICER) to prevent one case of diabetes was US$1052 with LSM, US$1095 with metformin, and US$1359 with the combination of both.…”
Section: Strategies For the Prevention Of Diabetesmentioning
confidence: 99%
“…Cost analyses of diabetes prevention in LMICs have been conducted from various perspectives, based on within-trial or simulation modelling studies [ 58 ], with some of the first analyses coming from the Indian Diabetes Prevention Programme (IDPP) [ 59 ]. In this trial, over the 3 years of the study, the incremental cost-effectiveness ratio (ICER) to prevent one case of diabetes was US$1052 with LSM, US$1095 with metformin, and US$1359 with the combination of both.…”
Section: Strategies For the Prevention Of Diabetesmentioning
confidence: 99%
“…Diabetes prevalence increases alongside healthcare expenses, straining the economy. Literature shows that type 2 diabetes-related healthcare costs have decreased economic activity and productivity (Chatterjee et al, 2011 ; Dahal et al, 2022 ; Seuring et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Asia is the major site of a rapidly emerging diabetes epidemic. Conservative estimates based on population growth and aging, and the rate of urbanization in Asia showed that India and China would remain the two countries with the highest rates of diabetes by 2030 8 .…”
Section: Introductionmentioning
confidence: 99%